Mechanistic Aspects of Microbe-Mediated Nanoparticle Synthesis - Ghosh, Shubhrima; Ahmad, Razi; Banerjee, Kamalika; AlAjmi, Mohamed Fahad; Rahman, Shakilur (Frontiers in Microbiology, 2021)
In recent times, nanoparticles have found increasing interest owing to their size, large surface areas, distinctive structures and unique properties, making them suitable for various industrial and biomedical applications. Biogenic synthesis of nanoparticles using microbes is a recent trend and a greener approach compared to physical and chemical methods of synthesis which demand higher costs, greater energy consumption, complex reaction conditions and ensue hazardous environmental impact. Several microorganisms are known to trap metals in-situ and convert them into elemental nanoparticles forms. They are found to accumulate inside and outside of the cell as well as in the periplasmic space. Despite the toxicity of nanoparticles, the driving factor for the production of nanoparticles inside microorganisms remains unelucidated. Several reports suggest that nanotization is a way of stress response and biodefense mechanism for the microbe which involves metal excretion/accumulation across membranes, enzymatic action, efflux pump systems, binding at peptides and precipitation. Moreover, genes also play an important role for microbial nanoparticle biosynthesis. The resistance of microbial cells to metal ions during inward and outward transportation leads to precipitation. Accordingly, it comes pertinent to understand the interaction of the metal ions with proteins, DNA, organelles, membranes and their subsequent cellular uptake. The elucidation of the mechanism also allows us to control the shape, size and monodispersity of the nanoparticles to develop large scale production according to the required application. This article reviews different means in microbial synthesis of nanoparticles focusing on understanding the cellular, biochemical and molecular mechanisms of nanotization of metals.